2006
DOI: 10.1073/pnas.0605452103
|View full text |Cite
|
Sign up to set email alerts
|

A redox-active FKBP-type immunophilin functions in accumulation of the photosystem II supercomplex in Arabidopsis thaliana

Abstract: Photosystem II (PSII) catalyzes the first of two photosynthetic reactions that convert sunlight into chemical energy. Native PSII is a supercomplex consisting of core and light-harvesting chlorophyll proteins. Although the structure of PSII has been resolved by x-ray crystallography, the mechanism underlying its assembly is poorly understood. Here, we report that an immunophilin of the chloroplast thylakoid lumen is required for accumulation of the PSII supercomplex in Arabidopsis thaliana. The immunophilin, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 37 publications
3
101
0
6
Order By: Relevance
“…The presence of such a large number of immunophilins with protein-folding capability suggests that these enzymes play a central role in the assembly and maintenance of protein complexes, such as the two photosystems whose subunits reside in or at least contact the thylakoid lumen. This possibility has been strengthened by a recent study showing a requirement for one of the FKBPs, 20-2, for the maintenance of PSII (13). The present study shows that a member of the other immunophilin family in the thylakoid lumen, a CYP, is essential for assembling and stabilizing PSII.…”
mentioning
confidence: 61%
“…The presence of such a large number of immunophilins with protein-folding capability suggests that these enzymes play a central role in the assembly and maintenance of protein complexes, such as the two photosystems whose subunits reside in or at least contact the thylakoid lumen. This possibility has been strengthened by a recent study showing a requirement for one of the FKBPs, 20-2, for the maintenance of PSII (13). The present study shows that a member of the other immunophilin family in the thylakoid lumen, a CYP, is essential for assembling and stabilizing PSII.…”
mentioning
confidence: 61%
“…LPA2 is only present in plants and absent in Chlamydomonas and cyanobacteria, suggesting that it evolved after the divergence of the land plant lineage or that it was lost in the other lineages. FKBP-2, a lumen-localized immunophilin, appears to play a role in the formation of PSII supercomplexes as in its absence the levels of PSII monomers and dimers are increased whereas accumulation of PSII supercomplexes is diminished (Lima et al, 2006). Thus a large number of factors participate in the assembly of a functional PSII complex.…”
Section: Psii Assembly Degradation and Repairmentioning
confidence: 99%
“…Peptidylprolyl isomerases act on protein imide bonds and are believed to coordinate protein folding, signal transduction, trafficking, assembly, and cell cycle regulation (Göthel and Marahiel, 1999). Interestingly, a member of this family has been shown to specifically modulate PSII complex formation (Lima et al, 2006) and the hypersalinity observed decrease could be associated with PSII FCP assembly changes.…”
Section: General Stress Response Proteinsmentioning
confidence: 99%